2016
DOI: 10.1200/jco.2015.64.6364
|View full text |Cite
|
Sign up to set email alerts
|

Successful Therapy Reduction and Intensification for Childhood Acute Lymphoblastic Leukemia Based on Minimal Residual Disease Monitoring: Study ALL10 From the Dutch Childhood Oncology Group

Abstract: Purpose Outcome of childhood acute lymphoblastic leukemia (ALL) improved greatly by intensifying chemotherapy for all patients. Minimal residual disease (MRD) levels during the first months predict outcome and may select patients for therapy reduction or intensification. Methods Patients 1 to 18 years old with ALL were stratified on the basis of MRD levels after the first and second course of chemotherapy. Thereafter, therapy was substantially reduced in patients with undetectable MRD (standard risk) and inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
292
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(323 citation statements)
references
References 44 publications
10
292
2
5
Order By: Relevance
“…7,42 With 5-year survival rates exceeding 90% in many developed countries, 33 current efforts are focused on the early identification of patients with highly curable leukemia to avoid short-term morbidity and mortality and long-term treatmentrelated sequelae. 12,13 In this regard, attainment of negative MRD after exposure to only a few drugs for a short duration of time (ie, 2 weeks from treatment initiation), is a very useful indicator. 10,43 This approach is particularly helpful in patients with t(12;21)/ ETV6-RUNX1 or hyperdiploid (.50 chromosomes) ALL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,42 With 5-year survival rates exceeding 90% in many developed countries, 33 current efforts are focused on the early identification of patients with highly curable leukemia to avoid short-term morbidity and mortality and long-term treatmentrelated sequelae. 12,13 In this regard, attainment of negative MRD after exposure to only a few drugs for a short duration of time (ie, 2 weeks from treatment initiation), is a very useful indicator. 10,43 This approach is particularly helpful in patients with t(12;21)/ ETV6-RUNX1 or hyperdiploid (.50 chromosomes) ALL.…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric oncologists treating children and adolescents with ALL have pioneered the use of MRD to monitor response to treatment, and all major pediatric oncology centers and cooperative groups worldwide now systematically use MRD levels to guide treatment decisions (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20] Because precise measurements of MRD have important prognostic and therapeutic implications, it is essential to understand their clinical significance in the context of presenting clinical and biologic features, treatment regimen, and time interval at which MRD is measured.…”
Section: Introductionmentioning
confidence: 99%
“…The main sources of vitamin D are production in the skin through sunlight exposure, diet, and vitamin D supplements [7,11]. Vitamin D (D 2 Children with ALL may be at increased risk of vitamin D deficiency due to impaired sun exposure and impaired vitamin intake [12]. A retrospective study in 86 pediatric cancer patients with a median age of 7 years revealed vitamin D deficiency in 63% at diagnosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Five-year EFS was 87%, with EFS of 88% in MRD mediumrisk patients (high end-induction/low second time point MRD) who received intensification and maintenance therapy similar to DFCI 05-001 HR patients. 31 This result suggests that, among the patients classified as VHR based on MRD on DFCI 05-001, incorporation of a second MRD time point may have discriminated between those who could be successfully treated as HR patients (with low second time point MRD) vs those requiring more intensified therapy.…”
mentioning
confidence: 98%
“…Others have shown that MRD measured at a second time point in therapy, 10 to 12 weeks after the start of treatment, is an important predictor of outcome. 7,14,31 The Italian Association of Pediatric Hematology Oncology-Berlin-Frankfurt-Munster ALL 2000 study used MRD assessment at 2 time points to stratify patients, with MRD assessment at days 33 and 78.…”
mentioning
confidence: 99%